A Container Production of Palms - Alan W. Meerow; Timothy K. Broschat (EDIS)
This document summarizes all the good practices for growing palms in containers. Container-grown palms are raised for essentially three markets: liners for field production wholesale or mass market retail sales for landscapes, and interior specimens, both mass market houseplants and interiorscape use.